Enhancing the Effectiveness of External Support in Building Tax Capacity in Developing Countries : Prepared for Submission to G20 Finance Ministers - International Monetary Fund (World Bank, Washington, DC, 2017)
This report responds to the February 2016 request from the G20. The report has been prepared in the framework of the Platform for Collaboration on Tax (the “PCT”), under the responsibility of the Secretariats and Staff of the four mandated organizations. The report reflects a broad consensus among these staff, but should not be regarded as the officially endorsed views of those organizations or of their member countries. The request arises in the context of increased recognition of the centrality to development of strong tax systems and of the importance of external support in building them, and a correspondingly increased willingness of advanced economies to provide substantially greater financing and other support for this. In that context, the report uses the experiences of the international organizations to analyze how support for developing tax capacity can be improved.